Clinical profile of malignancies of groin region in our area: a combined retrospective and prospective study - Bashir, Arshad; Rather, Shabir Hussain; Bhat, Showkat Ali; Nabi, Naveed; Zaman, Muzzafar (International Journal of Research in Medical Sciences, 2021)
Background: This study involved various malignancies affecting the groin area in all age group of patients and both genders. The aim of the study was to study the various types of malignancies affecting groin, viz. primary or metastatic, and to project their clinical profile. Methods: In this observational study, a total of 145 patients of groin malignancies were studied in department of General and Minimal Invasive Surgery and allied specialties in a tertiary care hospital. The study was retrospective from January 2005 to April 2012 and prospective from May 2012 till 2014. Results: Out of the total of 145 cases almost 95% were metastatic in the groin and primary groin cancers constituted only 4.9% of the cases. Out of 138 tumors that were metastatic in the groin 108 were squamous cell carcinomas followed by malignant melanoma in 28 cases. Most common predisposing factor for development of groin malignancy was use of kangri in our area. Conclusions: Most of the groin malignancies are metastatic to groin and primary cancers at groin are very rare. Kangri use in our part of the world, is the most important predisposing factor leading to squamous cell carcinoma. The management protocol followed in order to treat groin malignancy is surgery of the primary lesion and block dissection of groin.